Analisis Kadar Bahan Kimia Obat Dexametason Pada Jamu Reumatik Menggunakan Spektrofotometri Uv-Vis - Muhammad Taupik; A. Mu’thi Andy Suryadi; Endah Nurrohwinta Djuwarno; Faramita Hiola (Jambura Journal of Chemistry, 2022)
Traditional medicines are ingredients in the form of plant ingredients, animal ingredients, mineral substances, galenic, or mixtures of these ingredients that have been used for treatment from generation to generation and can be applied in accordance with the prevailing norms in society. One type of traditional medicine that is currently consumed by many people is herbal medicine. Jamu (empirical based herbal medicine) is a traditional medicine that is provided traditionally which contains all the plant ingredients that make up the herbal medicine which is hygienic (free of contamination) and is used traditionally. The research objective was to determine the presence of the chemical ingredient of dexamethasone drug in jamu for rheumatic and also to quantitatively determine the dexamethasone level in jamu for rheumatic by using uv-vis spectrophotometry. The results showed that all five jamu for rheumatic samples contained the chemical ingredient of dexamethasone drug with levels of each sample, namely jamu A 99,83 mg, jamu B 34,71 mg, jamu C 363,13 mg, jamu D 9,979 mg, and jamu E 778,97 mg